Modern tendencies in a thyroid volume of the newly born childrenin Tomsk and Tomsk Region - T. V. Davydova; E. B. Kravets (Бюллетень сибирской медицины, 2008)
The thyroid was ultrasonographically studied in 236 a newly born child aged 7-28 days of life in Tomsk and Tomsk Region. The sizes of thyroid lobes and its echogenicity were defermined. The infants were born by apparently healthy mothers and females, who took different dozes of iodine. A procedure for neonatal ultrasound study was developed. While data statistical processing individual dizes of ultrasonographical standard of a thyroid volume, which allows some patological conditions of the thyroid to be established at early stages of life were defesmined.